Pemidanaan Terhadap Pelaku Tindak Pidana Perdagangan Orang Sebagai Mata Pencaharian (Putusan Nomor 465/Pid.Sus/2021/PN.Ktp) : Pemidanaan Terhadap Pelaku Tindak Pidana Perdagangan Orang Sebagai Mata Pencaharian (Putusan Nomor 465/Pid.Sus/2021/PN.Ktp) - Matatula Zefanya Armando Doeputra; Ermania Widjajanti; Indonesia (Faculty of Law, Universitas Trisakti, 2024)
Law Number 21 of 2007 concerning the eradication of Criminal Acts of Human Traffcking (UU TPPO) regulates criminal acts ivolving human trafficking as a means of livelihood. The problems in this research are 1) Does the application of the provisions of Article 296 of the criminal code Article 2 of the TPPO law to perpetrators of criminal acts of human trafficking carried out as a means of livelihood in Decision Number 465/Pid.Sus/2021/PN.Ktp already in accordance with the purpose of the punishment? This research uses a normative research type with secondary data and is descriptive analytical in nature. Data analysis wa carried out qualitatively by drawing conclusions deduktively. The results and conclusions of this research are that the panel of judges wa inappropriate in using the provisions of Article 296 of the Criminal Code as a basis for consideration and decision for the criminal acts of human trafficking committed by the perperator. Furthermore, the punishment given to perpetrators of criminal acts of human trafficking which is carried out as a means of livelihood is not in accordane with the theories of punishment and criminal objectives, namely Reformation, Restraint, Retribution and Detterence (3R and 1D).